Genome-wide characteristics and potential functions of circular RNAs from the embryo muscle development in Chengkou mountain chicken - Zhang, Yang; Wang, Haiwei; Li, Xingqi; Yang, Chaowu; Yu, Chunlin; Cui, Zhifu; Liu, Anfang; Wang, Qigui; Liu, Lingbin (Frontiers in Veterinary Science, 2024)
The Chengkou Mountain Chicken, a native Chinese poultry breed, holds significant importance in the country's poultry sector due to its delectable meat and robust stress tolerance. Muscle growth and development are pivotal characteristics in poultry breeding, with muscle fiber development during the embryonic period crucial for determining inherent muscle growth potential. Extensive evidence indicates that non-coding RNAs (ncRNAs) play a regulatory role in muscle growth and development. Among ncRNAs, circular RNAs (circRNAs), characterized by a closed-loop structure, have been shown to modulate biological processes through the regulation of microRNAs (miRNAs).This study seeks to identify and characterize the spatiotemporal-specific expression of circRNAs during embryonic muscle development in Chengkou mountain chicken, and to construct the potential regulatory network of circRNAs-miRNA-mRNAs. The muscle fibers of HE-stained sections became more distinct, and their boundaries were more defined over time. Subsequent RNA sequencing of 12 samples from four periods generated 9,904 novel circRNAs, including 917 differentially expressed circRNAs. The WGCNA-identified circRNA source genes significantly enriched pathways related to cell fraction, cell growth, and muscle fiber growth regulation. Furthermore, a ceRNA network constructed using combined data of present and previous differentially expressed circRNAs, miRNA, and mRNA revealed that several circRNA transcripts regulate MYH1D, MYH1B, CAPZA1, and PERM1 proteins. These findings provide insight into the potential pathways and mechanisms through which circRNAs regulate embryonic muscle development in poultry, a theoretical support for trait improvement in domestic chickens.